2011
DOI: 10.1038/sc.2011.64
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic evaluation of the shoulder of spinal cord injured patients undergoing rehabilitation program

Abstract: Study design: Clinical and radiographic evaluation of the shoulders of tetraplegic and paraplegic patients who attend rehabilitation program. Objectives: The objective of this study is to establish the usefulness of radiography as a trial exam for shoulder pain in spinal cord injured patients. Setting: Hospital das ClinicasFUNICAMP. Campinas, Sao Paulo, Brazil. Methods: Thirty-two shoulders of 16 patients were evaluated by clinical exam and radiography. Patients were divided into two groups: paraplegic and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Results of correlation between level of SCI and shoulder pain are similar to published data [10,11,[14][15][16]. Furthermore, in our study, high thoracic SCI (T2-T7) patients have more chances of presenting shoulder pain.…”
Section: Discussionsupporting
confidence: 93%
“…Results of correlation between level of SCI and shoulder pain are similar to published data [10,11,[14][15][16]. Furthermore, in our study, high thoracic SCI (T2-T7) patients have more chances of presenting shoulder pain.…”
Section: Discussionsupporting
confidence: 93%
“…This is lower than prevalence of shoulder pain in the literature on persons with chronic SCI, which is found to be between 60 and 89%. 2,4,12,14,15 Unfortunately, these studies mostly do have a cross-sectional study design, use a different definition of shoulder pain (distinguish musculoskeletal and neuropathic pain), and use different outcome measures and/or include different populations and TSI. Therefore, comparison with prevalence of shoulder pain in our study should be interpreted with caution.…”
Section: Eriks-hoogland Et Al Trajectories Of Musculoskeletal Shouldmentioning
confidence: 99%
“…Age, gender, injury level, injury duration and the number of times moving from wheelchair onto bed and back factors which reported in previous research affect shoulder pain (23)(24)(25). Studies also indicated that the time passed after the injury and transferring from wheelchair to bed and back were considered as influential factors on shoulder pain (11,26).…”
Section: Discussionmentioning
confidence: 85%